A revision of Calodera Mannerheim. III. A new species from Russia and a key to the Palaearctic species of the genus (Coleoptera: Staphylinidae: Aleocharinae) - Assing, Volker (Zootaxa, 2003)
Calodera lunata sp. n. (Russia: Komi Republic) is described, illustrated, and distinguished from the Eastern Palaearctic C. zerchei Assing, 2003 and C. desdemona Sharp, 1888. Calodera hebeiensis Pace, 1999 is transferred to Parocyusa Bernhauer. A key to the Palaearctic species of Calodera is provided.